MEASUREMENT OF MACULAR THICKNESS AFTER PHACOEMULSIFICATION CATARACT SURGERY BY USING OPTICAL COHERENCE TOMOGRAPHY (World Bulletin of Public Health, 2022)
Cataract surgery often causes reduced visual acuity because of the cystoid macular edema. increased retinal thickness arises from breakdown of the blood–retinal barrier and subsequent accumulation of fluid with increased retinal thickness. Macular edema might be seen, measured, and assessed with optical coherencetomography since it produces two- or three-dimensional pictures of the retinal tissue and assesses the treatment's effectiveness. OBJECTIVE: to measure macular thickness after uneventful phacoemulsification cataract surgery using optical coherence tomography.
Keywords: uneventful; Cystoid; Cataract; surgery